Computational Fluid Dynamics Study Of Nasal Cavity Model - Riazuddin, Vizy Nazira (2011)
Understanding the properties of airflow in the nasal cavity is very important in determining the nasal physiology and in diagnosis of various anomalies associated with the nose. Inter-human anatomical variation for the nasal cavity exists and also differences on physiological morphology are observed based on gender. No specific numerical modeling studies have been carried out to compare and ascertain the effect of gender on flow variable inside the nasal cavity. Also numerical modeling involves various simplifications, for example the postural effect and appropriate boundary conditions which affect the outcome of the airflow studies. The present work involves development of three-dimensional nasal cavity models using computed tomographic images of healthy Malaysian females. A steady state continuity and Navier stoke equations were solved for both inspiratory and expiratory mechanism with flow rates ranging from 7.5 to 15 L/min as laminar and 20 to 40 L/min studies were simulated depicting turbulent flow conditions. Computational fluid dynamics (CFD) analysis provided effective visualization of the flow features inside the nasal cavity. The comparison between inspiratory and expiratory mechanism and the effect of different breathing rates on nasal function have been presented. The value of maximum wall shear stress at the vestibule region increased by more than 2000 % as the flow rate increased from 7.5 to 40 L/min. The complicated anatomy of the nasal cavity has been naturally designed to attain the physiological function desired to facilitate normal breathing. The xix current study has identified certain gender based anatomical and physiological differences. The use of computational fluid dynamic has assisted in the understanding of these differences which could not be earlier quantified based on mere medical observation and measurement devices. The influence of postural changes in nasal cavity has also been investigated. Around 0.3% change in the average static pressure is observed while changing from sitting to supine position. The change in the direction of gravity due to change of posture significantly influences the flow parameters and hence should be considered in all future studies involving nasal flow. Most of the researchers employ plug flow boundary definitions to address the flow problems associated with nasal flow. This study has revealed the fallacy of such a definition and found significant differences in values obtained in either case. Comparative study of the pull flow model and the plug flow model has found significant variations highlighting the need for using the right boundary conditions. At the nasal valve, the resistance for plug flow was 0.311 Pa-min/L and for pull flow the value was 0.147 Pa-min/L. Maximum variation was noticed at the vestibule region with 0.3578 Pa-min/L. The average velocity for nasal vestibule and nasal valve is 1.4m/s and 1.6m/s for plug flow. Whereas, for pull flow case, the average velocity value in nasal vestibule and nasal valve region was observed to be around 0.96m/s and 1.41m/s respectively. A correct approach therefore to the numerical model is the pull flow model, which more directly represents the physiological inspiratory mechanism.